Highly Accurate Brain Tumor Segmentation and Classification Using Multiple Feature Sets - Megha Sunil Borse; Murali Prasad R; Tummala Ranga Babu (Frontiers in Biomedical Technologies)
Purpose: Nowadays, detecting brain tumors is a crucial application. If a tumor is discovered later on, the medical issues are significant. Therefore, early diagnosis is essential. Magnetic Resonance Imaging (MRI) is the most recent detection, diagnosis, and assessment technology.